Impact of drip irrigation pipeline configuration and irrigation amount on fruit quality of densely planted dwarf Kuerle fragrant pear in Xinjiang - WANG Hongxin; WANG Chunxia; YUE Xuanli; LIN Ping; ZHANG Jingrui; ZHOU Fangyuan; LI Yanjie; WANG Yuan (Guan'gai paishui xuebao)
【Objective】 The Kuerle fragrant pear is a valuable cash crop in Xinjiang, with its production heavily relying on irrigation. This study investigates the influence of irrigation amount and drip irrigation pipeline configuration on its fruit quality. 【Method】 The experiment was conducted in an orchard, using the densely planted 7 year dwarf Kuerle fragrant pear as the model plant. Based on the number of drip irrigation pipelines per row of pear plants, three configurations were set up: 2 lines per row (P1), 3 lines per row (P2), and 4 lines per row (P3). Each configuration had two irrigation amount treatments: 6 750 m3/hm2 (W1) and 5 250 m3/hm2 (W2). For each treatment, we measured the spatiotemporal changes in soil water content and various fruit quality indices. 【Result】 Soil water content increased with soil depth, peaking at the depth of 70-90 cm before declining. The treatments did not significantly affect fruit hardness but had a notable impact on fruit weight and other quality indicators, including soluble sugar and vitamin C content. Under the same irrigation amount, an increase in the number of drip irrigation pipelines was associated with an increase in the longitudinal diameter of the fruits. When the irrigation amount was 6 750 m3/hm2, the vitamin C content in the fruits increased with the increase in the number of drip irrigation pipelines. Among all quality indices, the coefficient of variation for titratable acid and vitamin C content was the highest, both exceeding 30%. Correlation analysis revealed that fruit weight was positively correlated with longitudinal and transverse diameters of the fruits, as well as the solid-acid ratio, while negatively correlated with titratable acid, soluble sugar, and vitamin C content. 【Conclusion】 A comprehensive analysis indicated that the optimal drip irrigation scheme for Kuerle fragrant pear production in Xinjiang is three drip irrigation pipelines per row of pears plant, with an irrigation amount of 5 250 m3/hm2.